Systematic Literature Review: Turbine Types and Publication Trends in Micro-Hydro Power Plant Design Research - Rendy Putra Septiandra; Miftakhul Anwar Maulana; Muhammad Rifqi 'Imadul Haq; Nanda Putra Harianto; Moh Zainul Falah; Sujito, Sujito; Abdul Qader Hasan (Journal Electrical and Computer Experiences, 2024)
All human activities depend on electrical energy. The use of new renewable energy in Indonesia is still around 15%, even though Indonesia has great potential for new and renewable energy sources, especially water-based alternative energy. PLTMH is one example of the utilization of new renewable energy from water sources. Turbine is one of the important components in PLTMH. This study aims to conduct a literature review on turbine types and trends in PLTMH design publications using the systematic literature review method.  The review results show that the crossflow type impulse turbine is most dominantly used in PLTMH, followed by the Pelton type. Other turbine types such as Francis, Vortex, Archimedes Screw, and undershot are used less frequently. The publication trend peaked in 2020, then declined moderately in the following years. As of May 2024, there are no new studies, indicating a change in focus or a decline in interest.